Ethnic School Segregation and Second-generation Immigrants' Human Capital - Martin Nordin (Lund University, School of Economics and Management, Department of Economics, 2011)
Recent research has shown that there is a substantial skill difference in Sweden between natives and second-generation immigrants. The objective of this study is to find out whether there exists a relationship between ethnic school segregation and the individual's human capital. The variation in ethnic concentration rate between cohorts within a school generally does not affect the individual's human capital outcome. However when estimating specific peer influences between different ethnic groups (first-generation immigrants, second generation immigrants with two foreign-born parent and second generation immigrants with one foreign-born parent) the study shows three major findings. First, for men (both natives and second-generation immigrants) there is a general negative effect of having a large share of first-generation immigrant schoolmates. Second, for both men and women a large share of schoolmates with a completely foreign background (non-native parents) has a negative influence on the Swedish grades of second-generation immigrants with two foreign-born parents. Third, for men there seem to exist specific and positive peer influences within the groups of second-generation immigrants with either one or two foreign-born parents.
Keywords: I21; J24; 330; Ethnic Segregation; second-generation immigrants; human capital test score gap